High-throughput investigation of virulence gene regulation by sRNAs in Salmonella Typhimurium - Händler, Kristian (Trinity College (Dublin, Ireland). Department of Microbiology, 2015)
This study focused on novel gene regulatory systems in Salmonella enterics serovar Typhimurium, a model gram-negative, bacterial pathogen. The sRNA-mediated control of virulence genes was a particular emphasis. The research was designed to identify regulons controlled by sRNAs, in a high-throughput manner, and to determine any impact upon the orchestration of virulence gene expression.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin